The Discourse of the 1945 Indonesian Proclamation of Independence in Digital Spaces: A Semiotic Analysis of Digital Citizenship Literacy among Civic Education Students - Lianda Dewi Sartika; Anak Agung Ngurah Bagus Janitra Dewanta; Ayunda Wulandari (Lembaga Penerbitan dan Publikasi Ilmiah Yayasan Pendidikan Tumpuan Bangsa, 2026)
In an era of social media characterised by the rapid production and consumption of digital narratives, the discursive construction of the 1945 Indonesian Independence Proclamation is no longer confined to formal classrooms but is massively reconstructed through content on Instagram, TikTok, and YouTube, carrying ideological messages that potentially shape the civic understanding of the younger generation. This article examines that discursive construction using Roland Barthes' semiotic framework, encompassing denotative, connotative, and mythological layers of meaning, combined with a digital media literacy approach, while simultaneously investigating how PPKn students critically consume, interpret, and evaluate proclamation-related content. The study employs a qualitative approach with multimodal semiotic analysis as the primary method, supported by phenomenological interviews with purposively selected PPKn student informants. Data were collected through systematic documentation of proclamation-themed social media content and semi-structured in-depth interviews. The findings reveal that proclamation narratives on social media are predominantly constructed through nationalist-heroic myth frameworks, with significant gaps between the ideological messages encoded in the content and the critical interpretive capacity of PPKn students as civic actors. This research contributes to the intersection of semiotic studies, digital media literacy, and civic education, and recommends the integration of semiotic analysis competencies into PPKn curricula to strengthen students' capacity as critically literate digital citizens.